The Potential of Biologically Active Brazilian Plant Species as a Strategy to Search for Molecular Models for Mosquito Control - Valli, Marilia; Atanázio, Letícia Cristina Vieira; Monteiro, Gustavo Claro; Coelho, Roberta Ramos; Demarque, Daniel Pecoraro; Andricopulo, Adriano Defini; Espindola, Laila Salmen; Bolzani, Vanderlan da Silva (Planta Medica, 2020)
Natural products are a valuable source of biologically active compounds and continue to play an important role in modern drug discovery due to their great structural diversity and unique biological properties. Brazilian biodiversity is one of the most extensive in the world and could be an effective source of new chemical entities for drug discovery. Mosquitoes are vectors for the transmission of dengue, Zika, chikungunya, yellow fever, and many other diseases of public health importance. These diseases have a major impact on tropical and subtropical countries, and their incidence has increased dramatically in recent decades, reaching billions of people at risk worldwide. The prevention of these diseases is mainly through vector control, which is becoming more difficult because of the emergence of resistant mosquito populations to the chemical insecticides. Strategies to provide efficient and safe vector control are needed, and secondary metabolites from plant species from the Brazilian biodiversity, especially Cerrado, that are biologically active for mosquito control are herein highlighted. Also, this is a literature revision of targets as insights to promote advances in the task of developing active compounds for vector control. In view of the expansion and occurrence of arboviruses diseases worldwide, scientific reviews on bioactive natural products are important to provide molecular models for vector control and contribute with effective measures to reduce their incidence.
Keywords: Cerrado; Brazilian hotspot; natural products; molecular targets; arbovirus; Aedes aegypti